2023
DOI: 10.1097/jcma.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted versus open hepatectomy for liver tumors: Systematic review and meta-analysis

Abstract: Background: This meta-analysis was conducted to evaluate the effectiveness and safety of robot-assisted hepatectomy (RAH) versus open hepatectomy (OH) for liver tumors (LT). Methods: A computer-based literature search was conducted to identify all randomized or nonrandomized controlled trials of RAH and OH in the treatment of LT from January 2000 to July 2022. Study-specific effect sizes and their 95% confidence intervals (CIs) were combined to calculate the pooled values, using a fixed-effects or random-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
0
24
1
Order By: Relevance
“…9 Additionally, incomplete resection and/or positive surgical margin (PSM) is always the key cause of the failure after treatment. 6,8,11 In the current study, 13 the difference of wideness of resection-free margin between RH and OH did not reach the statistical significance. The authors found the wideness of resection-free margin was less but recurrence rate was lower in the RH group than OH group.…”
contrasting
confidence: 72%
See 4 more Smart Citations
“…9 Additionally, incomplete resection and/or positive surgical margin (PSM) is always the key cause of the failure after treatment. 6,8,11 In the current study, 13 the difference of wideness of resection-free margin between RH and OH did not reach the statistical significance. The authors found the wideness of resection-free margin was less but recurrence rate was lower in the RH group than OH group.…”
contrasting
confidence: 72%
“…13 In term of other parameters, such as resection-free margin (SMD −0.3 cm; 95% CI, −0.75 to −0.16), and the need of blood transfusion (OR, 1.01; 95% CI, 0.33-3.07) were similar between RH and OH groups. 13 Based on the aforementioned findings, the authors concluded that RH is safe and feasible in the treatment of HCC. 13 The current article is very interesting and worthy of further discussion.…”
mentioning
confidence: 80%
See 3 more Smart Citations